2021
DOI: 10.3390/pharmaceutics13111895
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology Applications of Flavonoids for Viral Diseases

Abstract: Recent years have witnessed the emergence of several viral diseases, including various zoonotic diseases such as the current pandemic caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Other viruses, which possess pandemic-causing potential include avian flu, Ebola, dengue, Zika, and Nipah virus, as well as the re-emergence of SARS (Severe Acute Respiratory Syndrome) and MERS (Middle East Respiratory Syndrome) coronaviruses. Notably, effective drugs or vaccines against these viruses ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 362 publications
(376 reference statements)
0
18
0
Order By: Relevance
“…Novel nanotechnologies mainly included nanoparticles, nanogel, nanocrystals, nanoemulsion, nanosuspension, micelles, liposome, solid lipid nanoparticles, self-nanoemulsifying drug delivery systems (SNEDDS), and self-micro-emulsifying drug delivery system (SMDDS) (Ahmad et al, 2016;Alothaid et al, 2021;Jain et al, 2021). Utilizing nanotechnology has created foremost progresses toward enhancing stability, bioavailability, delivery, sustained release, and therapeutic index of flavonoids (Ayala-Fuentes and Chavez-Santoscoy, 2021; Jannat et al, 2021). Considering the promising therapeutic effects of alpinetin, these novel nano-drug delivery systems as prospective approaches should be exploited to deliver alpinetin in a managed and specific way.…”
Section: Enhancement Strategiesmentioning
confidence: 99%
“…Novel nanotechnologies mainly included nanoparticles, nanogel, nanocrystals, nanoemulsion, nanosuspension, micelles, liposome, solid lipid nanoparticles, self-nanoemulsifying drug delivery systems (SNEDDS), and self-micro-emulsifying drug delivery system (SMDDS) (Ahmad et al, 2016;Alothaid et al, 2021;Jain et al, 2021). Utilizing nanotechnology has created foremost progresses toward enhancing stability, bioavailability, delivery, sustained release, and therapeutic index of flavonoids (Ayala-Fuentes and Chavez-Santoscoy, 2021; Jannat et al, 2021). Considering the promising therapeutic effects of alpinetin, these novel nano-drug delivery systems as prospective approaches should be exploited to deliver alpinetin in a managed and specific way.…”
Section: Enhancement Strategiesmentioning
confidence: 99%
“…Molecular docking studies showed that the compound (quercetin) has high binding affinities to various targets in SARS-CoV-2 [81], and can be a potential nutraceutical against COVID-19 [82][83][84]. It is evident that both diabetes and COVID-19 induce the over-production of reactive oxygen species, which ultimately may cause damage to many vital organs, including the kidney, heart, and lungs [17].…”
Section: Synergistic Kidney Damage and Morbidity Due To Covid-19 And ...mentioning
confidence: 99%
“…Flavonoids are natural polyphenolic compounds with antioxidant, anti-inflammatory, and antiviral properties, as well as protective effects on the gastrointestinal tract [ 379 , 380 , 381 , 382 ]. Apigenin, cyanidin, (-)-epigallocatechin-3-O-gallate (EGCG), genistein, kaempferol, luteolin, puerarin, and quercetin are all antioxidants ( Table 6 ); therefore, these compounds demonstrate an inverse relationship between oxidative stress and arthritis, with or without obesity [ 383 , 384 , 385 , 386 , 387 ].…”
Section: Obesity and Arthritis Managementmentioning
confidence: 99%